Eleutherine palmifolia (L.) Merr. Extract Increases The Crypts and Caspase-3 Expression in Colitis-Associated Colon Cancer Model - Roihatul Mutiah; Wahyi Yucha Firsyaradha; Riza Ambar Sari; Rahmi Annisa; Risma Aprinda Kristanti; Yen Yen Ari Indrawijaya; Tias Pramesti Griana; Anik Listiyana (Universitas Gadjah Mada, 2020)
It is known that Eleutherine palmifolia (L.) Merr contains flavonoid and polyphenol as bioactive compounds that have the ability as chemopreventive agents. This study aims to examine the effect of Eleutherine palmifolia (L.) Merr extract (EPE) on colon histopathology and the enhancement of caspase-3 expression in BALB/c mice of colitis-associated colon cancer (CAC) model. Thirty Balb/c female mice were used in this study and were divided into six groups. Five mice in one group were normal or negative control (given phosphate-buffered saline), and twenty-five mice were induced intraperitoneally with 10 mg/kg BW AOM (Azoxymethane), and it was followed by the administration of 5% DSS (Dextran Sodium Sulfate) every two weeks for 20 weeks. At the sixth week, one mice in each group was sacrificed for the Fecal Occult Bold Test (FOBT) and serum amyloid α (SAA) test to ensure that CAC was indeed formed. The administration of EPE with varying doses was started from the eighth week and was continued until the 21st week. The length of the colonic crypt was measured through histology appearance using Hematoxylin-eosin (HE) staining while the immunohistochemical method was used to observe apoptotic activity through the enhancement of caspase-3 expression. The results showed that the increase in EPE dosage also increased the crypt colon length compared to the positive control group. The administration of 1.00 mg/20gBW EPE significantly increased cell apoptosis which can be observed through caspase-3 expression compared to the positive control group (p<0.05). Based on these data, the extract of EPE can be developed as phytotherapy for chemopreventive.